2014
DOI: 10.3743/kosim.2014.31.3.227
|View full text |Cite
|
Sign up to set email alerts
|

The JASIST Editorial Board Members' Research Areas and Keywords of JASIST Research Articles

Abstract: This paper examines the characteristics of the JASIST (Journal of the Association for Information Science and Technology) editorial board members and their research areas through author co-citation analysis, and investigates whether the editorial board members' research areas are related with keywords frequently appeared in the journal's research articles. In the process, research areas of the central members and those appeared most frequently as keywords will be identified. Research areas of the 36 members on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These we attempt to explain from the perspective of changes in the editorial team. In the past 2 decades, JASIST has assigned different groups of editorial teams, and it is evident that journal editorial boards have to some extent set the pace of research topics (Kim, 2014; Walters, 2016), which have been proved in this study to be highly related to the choice of rhetorical structure. We do not speculate further on this matter here, but consider it as a limitation of the present paper and a target for further studies.…”
Section: Discussionmentioning
confidence: 80%
“…These we attempt to explain from the perspective of changes in the editorial team. In the past 2 decades, JASIST has assigned different groups of editorial teams, and it is evident that journal editorial boards have to some extent set the pace of research topics (Kim, 2014; Walters, 2016), which have been proved in this study to be highly related to the choice of rhetorical structure. We do not speculate further on this matter here, but consider it as a limitation of the present paper and a target for further studies.…”
Section: Discussionmentioning
confidence: 80%
“…They found that the most citations to JOD articles came from journals in library science, science, and social science. Kim (2014) examined the nature of research of the JASIST editorial board members and identified the relationship between the frequently‐used keywords of JASIST articles and the research areas of editorial board members. The research areas of 36 board members were collected and compared with 169 research articles published in JASIST in 2013.…”
Section: Literature Reviewmentioning
confidence: 99%